The Resistance of Cancer Cells to Palbociclib, a Cyclin-Dependent Kinase 4/6 Inhibitor, is Mediated by the ABCB1 Transporter - Fu, Han; Wu, Zhuo-Xun; Lei, Zi-Ning; Teng, Qiu-Xu; Yang, Yuqi; Ashby, Charles R.; Lei, Yixiong; Lian, Yuyin; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
Palbociclib was approved by the U.S. Food and Drug Administration for use, in combination with letrozole, as a first-line treatment for estrogen receptor-positive/human epidermal growth factor receptor 2-negative (ER+/HER2-) postmenopausal metastatic breast cancer. However, recent studies show that palbociclib may be an inhibitor of the ABCB1 transporter, although this remains to be elucidated. Therefore, we conducted experiments to determine the interaction of palbociclib with the ABCB1 transporter. Our in vitro results indicated that the efficacy of palbociclib was significantly decreased in the ABCB1-overexpressing cell lines. Furthermore, the resistance of ABCB1-overexpressing cells to palbociclib was reversed by 3 μM of the ABCB1 inhibitor, verapamil. Moreover, the incubation of ABCB1-overexpressing KB-C2 and SW620/Ad300 cells with up to 5 μM of palbociclib for 72 h, significantly upregulated the protein expression of ABCB1. The incubation of KB-C2 cells with 3 μM of palbociclib for 2 h, significantly increased the intracellular accumulation of [3H]-paclitaxel, a substrate of ABCB1 but not in the corresponding non-resistant parental cell line, KB-3-1. However, the incubation of KB-C2 cells with 3 μM of palbociclib for 72 h decreased the intracellular accumulation of [3H]-paclitaxel due to an increase in the expression of the ABCB1 protein. Palbociclib produced a concentration-dependent increase in the basal ATPase activity of the ABCB1 transporter (EC50 = 0.549 μM). Molecular docking data indicated that palbociclib had a high binding affinity for the ABCB1 transporter at the substratebinding site, suggesting that palbociclib may compete with other ABCB1 substrates for the substrate binding site of the ABCB1. Overall, our results indicate that palbociclib is a substrate for the ABCB1 transporter and that its in vitro anticancer efficacy is significantly decreased in cancer cells overexpressing the ABCB1.